2010
DOI: 10.1108/09596111011018205
|View full text |Cite
|
Sign up to set email alerts
|

CSR among Canadian mass tour operators: good awareness but little action

Abstract: Purpose -The purpose of this paper is to provide an exploratory case study of mass mainstream tour operators in the Canadian market and evaluate their awareness level of corporate social responsibility (CSR) activities. The research aims to address the structure and ownership of mass Canadian tour operators, how it may influence the adoption of CSR practices, key issues and concerns and awareness level and participation of CSR practices. Although the Canadian outbound leisure mass market is relatively small co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 30 publications
4
94
1
4
Order By: Relevance
“…Additionally, the lack of firm evidence for any beneficial impact upon competiveness and financial performance [45] may serve to discourage companies that are driven by shortsighted financial goals [46]. Companies may be concerned about the time lag between investment in CSR practices and potential for return because CSR is regarded as a long-term investment [47].…”
Section: Drivers and Deterrents For Responsible Innovationmentioning
confidence: 99%
“…Additionally, the lack of firm evidence for any beneficial impact upon competiveness and financial performance [45] may serve to discourage companies that are driven by shortsighted financial goals [46]. Companies may be concerned about the time lag between investment in CSR practices and potential for return because CSR is regarded as a long-term investment [47].…”
Section: Drivers and Deterrents For Responsible Innovationmentioning
confidence: 99%
“…Weeden (2002) suggested that this can be achieved by ensuring that practices are transparent and can be viewed by all stakeholders, shareholders, employees and communities (Wheeler, 1990(Wheeler, , 1991. Significant research has emerged about CSR behaviour and ethics among tourism and hospitality enterprises (see Ayuso, 2006Ayuso, , 2007Bohdanowicz, Simanic, & Martinac, 2005;Dodds & Kuehnel, 2010;Kasim, 2006;Merwe & Wöcke, 2007, among others). Inevitably, there were questions which are still relatively unanswered; whether the tourism sector differs from other industries over CSR and its implementation.…”
Section: The Csr Languagementioning
confidence: 99%
“…Dodds & Kuehnel, 2010;Graci, 2009;Graci & Dodds, 2008Holcomb, Upchurch, & Okumus, 2007) it may appear that this area of study still remains relatively under-researched, particularly when considering research which links hospitality enterprises and strategic CSR. Of course, there are different opinions and perceptions about what should be the locus of interest in tourism management.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the environmental element of CSR, the level and type of 8 research has increased significantly in the last decade with studies highlighting CSR features in tourism such as eco-tourism (Chiu, Lee & Chen, 2014), museums and heritage (Edwards, 2007), mass tourism (Weaver, 2014), tour operators and airlines industry (Dodds & Kuehnel, 2010;Coles, Fenclova & Dinana, 2011), leisure and sport (Salome, van Bottenburg & van den Heuvel, 2013) and destinations (Frey & George, 2010;Liu et al, 2014). Work exploring the marketing of tourism also notes a shift towards sustainability away from economic profit priorities (Jamrozy, 2007) and the linkages between CSR and CFP have also been studied within tourism.…”
Section: Csr In Tourismmentioning
confidence: 99%